Enhancing Literacy and Educational Inclusion through Human-Centered Design of the PELITA Interactive Audio Table Game - Fahrobby Adnan; Januar Adi Putra; Abd. Mu’iz Samsul Arifin; Richie Olajuwon Santoso; Dea Novela Ramadani; Aprillia Bliesy; Fabian Nabil; Syahrial Rafky (Wikrama Parahita : Jurnal Pengabdian Masyarakat, 2026)
Educational inequality for persons with disabilities in Indonesia remains a major challenge, with approximately 40% of individuals with disabilities never having received formal education, while visual impairment represents the highest disability category, at 64%. Despite the increasing number of Special Education Schools (Sekolah Luar Biasa/SLB), many schools, including SLB Negeri Jember, still rely on conventional and monotonous teaching methods with limited interactive learning facilities, creating a gap between the learning needs of visually impaired students and existing educational solutions. This community service project developed PELITA (Personalized Ethnographic Learning with Interactive Table-Based Audio Game), an audio game–based educational platform designed to improve inclusive learning experiences for visually impaired students. The project applied a participatory community engagement approach involving teachers, students, parents, and school administrators through field observations, focus group discussions, co-design activities, product trials and iterative evaluations. PELITA was developed using the Octalysis Framework for gamification and integrates a joystick, touchpad keyboard, mini PC, stereo speakers, and monitor to support interactive and contextual learning based on real-life scenarios. Product testing involving visually impaired students demonstrated improvements in spatial orientation ability (37.1%), fine motor skills (22.1%), listening ability (24.3%), problem solving(29.2%), self-confidence(36.5%), social interaction(22.4%), and learning motivation (39.1%). These findings indicate that gamification-based assistive technology can effectively support inclusive education and provide adaptive learning experiences for students with visual impairment. Furthermore, PELITA offers a scalable and replicable innovation model that can be implemented in other regions through collaboration among schools, universities, local governments, and communities by adapting ethnographic learning content to local cultural contexts.